Older Adults With Cognitive and/or Physical Impairments Can Benefit From Immersive Virtual Reality Experiences: A Feasibility Study - Appel, Lora; Appel, Eva; Bogler, Orly; Wiseman, Micaela; Cohen, Leedan; Ein, Natalie; Abrams, Howard B.; Campos, Jennifer L. (Frontiers in Medicine, 2020)
Background: Older adults living in long term care and rehabilitation hospitals often experience reduced mobility, sometimes resulting in confinement indoors and isolation, which can introduce or aggravate symptoms of depression, anxiety, loneliness, and apathy. As Virtual Reality (VR) becomes increasingly accessible and affordable, there is a unique opportunity to enable older adults to escape their restricted physical realities and be transported to stimulating and calming places which may improve their general wellbeing. To date no robust evaluations of immersive VR-therapy (experienced through a head-mounted-display (HMD)) for older adults within these settings have been reported. VR-therapy may prove to be a safe, inexpensive, non-pharmacological means of managing depressive symptoms and providing engagement and enjoyment to this rapidly growing demographic. Objectives: Establish the feasibility of immersive VR-therapy for older adults with reduced sensory, mobility and/or impaired cognition. This includes evaluation of tolerability, comfort, and ease of use of the HMD, and of the potential for immersive VR to provide enjoyment/relaxation and reduce anxiety and depressive symptoms. Methods: Sixty-six older adults (mean age 80.5) with varying cognitive abilities (normal=28, mild impairment=17, moderate impairment=12, severe impairment=3, unknown=6), and/or physical impairments, entered a multi-site non-randomized interventional study in Toronto, Canada. Participants experienced 3 to 20 minutes of 360°-video footage of nature scenes displayed on Samsung-GearVR-HMD. Data was collected through pre/post-intervention surveys, standardized observations during intervention, and post-intervention semi-structured interviews addressing the VR experience. Results: All participants completed the study with no negative side-effects (e.g. no dizziness, disorientation, interference with hearing aids); the average time spent in VR was eight minutes and 76% of participants viewed the entire experience at least once. Participants tolerated the HMD very well; most had positive feedback, feeling more relaxed and adventurous; 76% wanted to try VR again. Better image quality and increased narrative video content were suggested to improve the experience. Conclusion: It is feasible and safe to expose older adults with cognitive and physical impairments to immersive VR within these settings. Further research should evaluate the potential benefits of VR in different settings (e.g. home/community based) and explore better customization/optimization of the content and equipment for the targeted populations.